2009
DOI: 10.1002/chin.200913149
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Ethyl Pyrimidine‐4‐carboxylates from Unsymmetrical Enamino Diketones and Their Application in the First Synthesis of Pyrimido[4,5‐d]pyridazin‐8(7H)‐ones

Abstract: Synthesis of Pyrimido[4,5-d]pyridazin-8(7H)-ones -[as products of agrochemical and pharmacological interest]. -(ROSA, F. A.; MACHADO, P.; FISS, G. F.; VARGAS, P. S.; FERNANDES, T. S.; BONACORSO, H. G.; ZANATTA, N.; MARTINS*, M. A. P.; Synthesis 2008, 22, 3639-3648; Dep. Quim., Univ. Fed. Santa Maria, 97105 Santa Maria, Brazil; Eng.) -Mais 13-149

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…An interesting study revealed that their condensation with NCN binucleophiles, e.g. benzamidine, could occur at both competing carbonyl groups and, therefore, could result in the formation of pyrimidine-4-carboxylate 56 (the major or the only product in most cases) or pyrimidine-5-glyoxylate 57 (Table 7) [134]. The observed regioselectivity could be explained by the more electrophilic nature of the carbonyl group adjacent to the ester moiety as compared to the benzoyl-type fragment, with an exception of CF3-substituted ketone moiety.…”
Section: β-Alkoxyvinyl-and β-Enamino α-Ketoestersmentioning
confidence: 99%
“…An interesting study revealed that their condensation with NCN binucleophiles, e.g. benzamidine, could occur at both competing carbonyl groups and, therefore, could result in the formation of pyrimidine-4-carboxylate 56 (the major or the only product in most cases) or pyrimidine-5-glyoxylate 57 (Table 7) [134]. The observed regioselectivity could be explained by the more electrophilic nature of the carbonyl group adjacent to the ester moiety as compared to the benzoyl-type fragment, with an exception of CF3-substituted ketone moiety.…”
Section: β-Alkoxyvinyl-and β-Enamino α-Ketoestersmentioning
confidence: 99%